Breast Cancer and the Immune System - Standish, Leanna J. (2008)
This article reviews the evidence that the functioning of both the innate and the adaptive immune system plays a role in preventing relapse in women with breast cancer. Lymphocytes, including T cells, T regulatory cells, and natural killer cells, and their cytokine release patterns are implicated in both primary prevention and recurrence of breast cancer. Cancer prognosis may be related to immune system functional status. The hypothesis that the immune system has a causal role in breast cancer etiology is supported by epidemiologic, preclinical, and clinical research. Empirical support for the concept that immune status and immunomodulatory therapy have important roles in comprehensive breast cancer treatment is provided.